Constructing children's physical education experiences : understanding the content for teaching - Allison, Pamela C.; Barrett, Kate R. (Boston : c)
Constructing Children's Physical Education Experiences encompasses the philosophical approach to teaching physical education called the Movement Approach, which is supported by constructivist education principles. This book introduces the preservice teacher to elementary school physical education by focusing on philosophy and content. Readers will learn to connect what they teach to why they teach it by applying constructivist learning theory to movement content. This book will prepare preservice teachers to work with children in their field experiences and student teaching, while giving them the tools they need to continue their own professional learning. For pre- and in-service teachers in elementary school physical education.
Includes index.
Keywords: Physical education teachers -- Training of; Physical education for children -- Study and teaching; Constructivism (Education).